Cybersecurity Policymaking in the BRICS Countries: From Addressing National Priorities to Seeking International Cooperation - Luca Belli (The African Journal of Information and Communication, 2021)
In the concluding statement of the 2021 BRICS Summit, the bloc’s five members—Brazil, Russia, India, China, and South Africa—pledged to pursue enhanced cooperation on cybersecurity issues, including by “establishing legal frameworks of cooperation among BRICS” and a BRICS intergovernmental agreement on cybersecurity. This piece briefly outlines the mounting relevance of cybersecurity for the BRICS countries, recent national policymaking in this area in the bloc, and the dynamics at play as the BRICS countries seek to further intensify and structure their cooperation on cybersecurity matters.